A Rare Clinical Presentation of Left Vulval Verrucous Cancer (Figo Stage 3): Image in Medicine - Jyoti Dwivedi; Deepali Ghungrud; Swapna Morey; Arti Raut; Samruddhi Gujar (Journal of Clinical and Diagnostic Research)
A 40-year-old perimenopausal female P1L1 with exophytic growth over the vulval region was admitted to the hospital with a history of discharge from the vagina. The patient was apparently healthy six months ago. After which, she started experiencing exophytic growth progressive in nature, with foul-smelling discharge. She complained of decreased appetite and weight loss. Also, she had complained of urinary retention for the last six months.